2014
DOI: 10.1016/j.clbc.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A Good Drug Made Better: The Fulvestrant Dose-Response Story

Abstract: Sequential use of endocrine therapies remains the cornerstone of treatment for hormone receptor-positive advanced breast cancer, before the use of cytotoxic chemotherapy for unresponsive disease. Fulvestrant is an estrogen receptor (ER) antagonist approved for the treatment of postmenopausal women with ER+ advanced breast cancer after failure of prior antiestrogen therapy. Initially approved at a monthly dose of 250 mg, the recommended fulvestrant dose was revised to 500 mg (500 mg/mo plus 500 mg on day 14 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 42 publications
0
64
0
Order By: Relevance
“…Thus, a strategy already underway is the improvement of pharmacokinetic properties to increase the internal exposure of tumors to highly potent antagonists. Some emerging orally active antiestrogens, such as AZD-9496, GDC-0810, as well as others, appear to provide just such encouraging behavior 34,63,8795 although further studies are needed regarding side-effect profiles and prevention of disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a strategy already underway is the improvement of pharmacokinetic properties to increase the internal exposure of tumors to highly potent antagonists. Some emerging orally active antiestrogens, such as AZD-9496, GDC-0810, as well as others, appear to provide just such encouraging behavior 34,63,8795 although further studies are needed regarding side-effect profiles and prevention of disease recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The poor pharmacokinetic properties of ICI 182,780 may limit its effectiveness in the clinic; indeed, increasing monthly intra-muscular injections of fulvestrant from 250 mg to 500 mg led to significant gains in overall survival in metastatic patients having recurred or progressed after prior endocrine therapy in the CONFIRM study and resulted in subsequent adoption of this regimen in the clinic (Di Leo et al . 2010, 2014, Robertson et al . 2014).…”
Section: Serms Vs Serds: Two Separate Classes Of Antiestrogens?mentioning
confidence: 99%
“…Currently, fulvestrant (Faslodex, AstraZeneca) is the only approved SERD for the treatment of postmenopausal women with advanced ER þ breast cancer who have progressed on endocrine therapies (http://www.accessdata.fda.gov/drugsatfda_docs/ label/2011/021344s015lbl.pdf). In the metastatic setting, fulvestrant has been shown to be effective as a single agent and a recent study demonstrated that the increased dose of 500 mg fulvestrant is superior to the historical 250 mg dose in terms of overall survival (8,12,13). However, there is evidence to suggest that even at the 500 mg dose, suboptimal occupancy of the estrogen receptor can occur in some patients, which may correlate with an earlier progression of disease (14).…”
Section: Introductionmentioning
confidence: 99%